Bathymetric observations of an extreme tidal flow: Approaches to the Gulf of Corryvreckan, western Scotland, UK. (15th March 2021) - Armstrong, Christian; Howe, John A.; Dale, Andrew; Allen, Christopher
Abstract: The growing interest in tidal energy has led to a need to better understand the interaction between energetic tidal flows and submarine bathymetry. The Gulf of Corryvreckan (GoC) is a highly energetic tidal channel, ∼3.2 km long and ∼1.1 km wide with a maximum depth of 220 m occurring between the islands of Scarba and Jura, western Scotland, UK. A high-resolution bathymetric survey of the region, groundtruthed by sediment samples, has enabled the bathymetry to be related to Lagrangian flow data from GPS-tracked surface drifter buoys. The maximum recorded drifter velocity was 4.75m/s within the GoC during the ebb (east-flowing) tide. Exiting the GoC into open water to the west on the flood tide, the 'Great Race' decelerates and subsequently flows in a curve to the north. East and west of the GoC, sedimentary bedforms lie on the flanks of the main flow paths. The northern flank of the Great Race aligns with a 6 km elongate bedform ('banner bank') extending from the GoC. East of the GoC, complex tidal bottom flows are suspected to result in uncommon sediment morphology, including suspected sediment wave interference patterns expressed by the mobile bedforms. The novelty of these findings indicates the importance of further research into sediment pathways in energetic tidal zones. A greater understanding of how sediment transport may be modified during offshore construction is an important consideration for offshore installations and the feasibility of marine renewables. Highlights: Constraining bathymetry significantly accelerates tidal flow speeds. Surface hydrodynamics inferred by GPS tracked drifters can reflect the local bathymetry, even in deeper (>100 m) shelf waters. The nature of submarine bedforms may be indicative of dominant bottom flow paths and residual tidal currents. Complex coastlines promote intricate residual tidal currents and sediment transport pathways, producing structurally uncommon submarine bedforms.